2018
DOI: 10.1016/j.tiv.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Manganese exposure: Linking down-regulation of miRNA-7 and miRNA-433 with α-synuclein overexpression and risk of idiopathic Parkinson's disease

Abstract: Manganese is an essential trace element however elevated environmental and occupational exposure to this element has been correlated with neurotoxicity symptoms clinically identical to idiopathic Parkinson's disease. In the present study we chronically exposed human neuroblastoma SH-SY5Y cells to manganese (100μM) and carried out expression profiling of miRNAs known to modulate neuronal differentiation and neurodegeneration. The miRNA PCR array results reveal alterations in expression levels of miRNAs, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…MiR-7 was reported to bind the 3’ UTR of SNCA and inhibited its translation, which was confirmed in our study [ 20 ]. Tarale et al proved that the low level of miR-7 implied a higher risk of idiopathic PD [ 21 ]. Zhou et al suggested that miR-7 inhibited neuroinflammation in the pathogenesis of PD through targeting Nod-like receptors [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-7 was reported to bind the 3’ UTR of SNCA and inhibited its translation, which was confirmed in our study [ 20 ]. Tarale et al proved that the low level of miR-7 implied a higher risk of idiopathic PD [ 21 ]. Zhou et al suggested that miR-7 inhibited neuroinflammation in the pathogenesis of PD through targeting Nod-like receptors [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In workers at an electric‐furnace steel plant, exposure to metal‐rich particulate matter was found to modify the expression of candidate miRNAs, which then leads to neurodegenerative diseases such as AD and PD . in vitro cells, Mn exposure was proved to upregulate the expression of α‐synuclein and fibroblast growth factor 20 by diminishing miR‐7 and miR‐433 levels, thereby increasing the risk of idiopathic Parkinson's disease . Another report also demonstrated that 73 kinds of miRNA expressions were altered following excessive Mn treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that upregulation of autophagy exerts neuroprotective effect, whereas dysfunctional autophagy is closely related to neurodegenerative diseases . It has been demonstrated that Mn can activate autophagy by triggering extracellular regulatory protein kinase (ERK1/2) and c‐Jun N‐terminal kinase (JNK) or inhibiting Akt signaling pathway . Activation of autophagy and abnormal aggregation of α‐synuclein in the brain tissue were also detected after mice subcutaneously injected with MnCl 2 for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mn deficiency has been related to impairments or dysfunctions in lipoprotein metabolism, insulin production, oxidant defense system, and growth factor metabolism (Keen et al. 1999; Tarale et al. 2018).…”
Section: Discussionmentioning
confidence: 99%